Cosmic ray dose monitoring using RadFET sensors of the Rosetta instruments SESAME and COSIMA. (August 2016) - Falke, Peter; Fischer, Hans-Herbert; Seidensticker, Klaus J.; Thiel, Klaus; Fischer, Henning; Hilchenbach, Martin; Henkel, Hartmut; Koch, Andreas
Abstract: On its more than 10 years journey to comet 67P/Churyumov–Gerasimenko, Rosetta carried RadFET ionising dose monitors in the central electronics of the orbiter instrument COSIMA and the lander instrument SESAME. The readings of the dosimeters were corrected for the temperature of the devices during measurements. Because the sensitivity of RadFETs depends on the energy of impinging charged particles, a mean efficiency factor for the prevalent proton radiation was determined by applying nine efficiency models to proton energy spectra of Rosetta's radiation environment. The resulting dose profiles show linear increases of the accumulated dose with time, mainly caused by galactic cosmic radiation, and the arrival of two solar particle events in 2005. The accumulated dose (in Silicon) during 3909 days in space from 2004-03-02 to 2014-11-14 was 3.2 ± 0.6 Gy in case of COSIMA and 1.9 ± 0.4 Gy for SESAME. The deviation of the two measurements is mainly due to the solar particle event in September 2005, which had a 5.3 ± 1.0 times stronger impact on the COSIMA RadFET. Measured dose levels are one order of magnitude lower than those expected before launch for not being exceeded on the 90% confidence level, which is mainly due to the low solar activity during the mission so far. Abstract : Highlights: The efficiency of RadFET dosimeters for Rosetta's radiation environment was determined. Ionising dose in central electronics of two payloads was measured during Rosetta's cruise to comet 67P/Churyumov–Gerasimenko. Galactic and solar cosmic rays contributed to the accumulated ionising dose. The relatively low contribution from solar particles was created by two solar particle events in 2005.